TRANSPARANSI DALAM PENYELENGGARAAN PELAYANAN PUBLIK - Mita Widyastuti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2009)
This article attempts to highlight public service organization that is still considered very poor or unsatisfactory. Poor service quality is rooted in the cultural bureaucrats (ambtennar) which in the colonial period tend to be served than serve. In addition, the absence of service standards, do not have the vision and mission. Those issues need to be addressed in various ways. One of them by making the service transparent, accountable and reliable.